2007
DOI: 10.1002/ijc.22629
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus and classical Hodgkin lymphoma: No evidence for a direct association

Abstract: A proportion of Hodgkin lymphoma (HL) cases are causally associated with the Epstein-Barr virus (EBV) but the aetiology of the remaining cases remains obscure. Over the last 3 decades several studies have found an association between HL and measles virus (MV) including a recent cohort study describing the detection of MV antigens in Hodgkin and Reed-Sternberg cells, the tumour cells in HL. In the present study we looked at the relationship between history of MV infection and risk of developing HL in a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
2
17
2
Order By: Relevance
“…31 Extensive studies based on serology or viral load have not yet identified an association between any specific known infectious agent and EBV-negative YAHL. [11][12][13][14][15][16] Although our study could not rule out a protective advantage after specific childhood exanthemata or other infections, risk was strongly reduced in the member of the twin pair who had more behaviors associated with oral-oral or fecal-oral exposure. Behaviors that increase oral exposures are risk factors for all infections transmitted by the fecal-oral or oral-oral route including but not limited to hepatitis A, Helicobacter pylori, Salmonella, and herpes simplex type 1.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…31 Extensive studies based on serology or viral load have not yet identified an association between any specific known infectious agent and EBV-negative YAHL. [11][12][13][14][15][16] Although our study could not rule out a protective advantage after specific childhood exanthemata or other infections, risk was strongly reduced in the member of the twin pair who had more behaviors associated with oral-oral or fecal-oral exposure. Behaviors that increase oral exposures are risk factors for all infections transmitted by the fecal-oral or oral-oral route including but not limited to hepatitis A, Helicobacter pylori, Salmonella, and herpes simplex type 1.…”
Section: Discussioncontrasting
confidence: 57%
“…8 However, extensive searches have yet to identify a viral agent that could account for the majority of YAHL. [11][12][13][14][15][16] Epstein-Barr virus is etiologically linked only to that small proportion of YAHL with EBV evident in the malignant cells. 4,10 An alternative hypothesis was first offered to explain the recent increase in the prevalence of atopic disease.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] An alternative explanation for the YAHL risk pattern (which is similar to that for atopy) is that relative social isolation in early childhood results in a deficit of generic microbial signals (ie, endotoxin) necessary for the normal maturation of the immune response ("hygiene hypothesis"). 33 In the gut lymphoid tissue, these microbial signals are thought to bind to toll-like receptors resulting in secretion of IL-12, which in turn induces the differentiation of Th1 lymphocytes necessary to mount cellmediated, cytotoxic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Also detection of EBV in HL in most Asian countries are less in young adults and are more detectable in children and older ages. Because of these differences infectious cofactors other than EBV have been suggested, but no consensus in support of any other particular association have emerge (Wilson, et al, 2007). …”
Section: Environmentmentioning
confidence: 99%